Scale dynamics of the HIDROPIXEL high-resolution DEM-based distributed hydrologic modeling approach. (May 2020) - Veeck, Sarah; da Costa, Fagner França; Correia Lima, Deborah Lopes; da Paz, Adriano Rolim; Allasia Piccilli, Daniel Gustavo
Abstract: The HIDROPIXEL high-resolution pixel-to-pixel distributed hydrological simulation approach was proposed based on digital elevation model (DEM) and adaptations of the curve number and unit hydrograph methods. This paper presents a reference evaluation of HIDROPIXEL, showing how sensible the model is to spatial resolution and assessing the effect of different DEM data sources. A small peri-urban Brazilian catchment ( 6 km 2 ) is studied using a 1 m LiDAR DEM ( 6 million pixels) and aggregated 2 m, 10 m, and 30 m, and SRTM 30 m resolutions. Peak flows were satisfactorily reproduced, with model performance decreasing with the spatial resolution coarsening, which tended to shorten the flow paths and underestimate the drainage area. For short and concentrated rain events, peak times were anticipated. Best results were obtained by adjusting the initial losses parameter. This methodology could easily be applied to other catchments, incorporating high-resolution DEM and simulating both land-use changes and spatial rainfall variability. Highlights: HIDROPIXEL high-resolution pixel-to-pixel distributed hydrological simulation approach aimed for scarce data regions. Based on the digital elevation model (DEM) processing and adaptations of the CN and unit hydrograph methods. Take advantage of high-resolution DEM and simulate land-use changes and the effect of spatial rainfall variability. Observed peak flows satisfactorily reproduced, with model performance decreasing with the spatial resolution coarsening.